PELAKSANAAN TERTIB ADMINISTRASI KEPENDUDUKAN PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN ROKAN HULU (STUDI KASUS AKTA KELAHIRAN) - Ausi Sunardi; Ernawati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Implementation orderly population administration Department of Population and Civil Registration Rokan Hulu (Birth Certificate Case Study). Administration implemented by the government apparatus in settlement arise of birth certificate is not in accordance with a predetermined time. Employees do not serve applicants who apply and do not check the exact requirements and thorough file and not socialized to people about making birth certificates.This study uses the theory Hadari Mawawi on the theory there are 3 variables that include speed, accuracy and transparency / open. Furthermore, the factors that affect the implementation orderly population administration in the department of population and civil registration Rokan Hulu regency (Birth Certificate Case Studies), namely leadership, communication, and human resources. This study used a qualitative approach.The results of this study according to the theoretical concept of speed, accuracy and transparency is not very good for the field of population administration. It can be seen from three variables: the speed is not in accordance with a predetermined time, the accuracy of which the results showed serve the public transparent from the study found that lack of explanation and lack of socialization. While there are three factors that the problem is communication, so the lack of administrative staff to provide information to the public so they do not know the procedure for the birth certificate.Keywords: Order Administration, Population, Birth Certificates